Positive Discrimination In the Electoral Process Analytical Study in View of The Rules of International and National Laws - Ahmed, Sirwan Hamd; Saeed, Zana Jalal (Journal of Legal and Political Studies, 2020)
Positive discrimination in the electoral process in favor of some components and groups, may be required by the requirements of the stage, especially in transitional democracies, until the legal and realistic status of these components and groups is stabilized, and they can defend their rights, exercise their freedoms, and participate naturally in the political process, so put positive discrimination primarily in order to protect some Components and categories. However, this procedure must be organized in a way that does not harm the society with it, and does not lead to discontent and resentment of others, because its aim is political and social sharing and harmony, so it should not be organized in a manner that does not serve its goal, but opposes it. Therefore, we find that the constitutions and laws that include this procedure have taken great care to achieve its goal and reach its goals. We in this research have depended a lot on clarifying and discussing the constitutional and legal organization of positive discrimination in the electoral process, reviewing the positives and negatives of this organization, based on the goal of the positive discrimination itself and the wisdom of its legislation. Through a balance between the interests of the positively distinguished groups and the interests and rights of other groups of society, we reached legal conclusions and remedies, so we proposed to the legislator and government institutions the necessary solutions and mechanisms, which lead to the implementation of this procedure, and to achieving the goal for which he developed and legislated.
Keywords: Positive discrimination; transitional democracies; realistic status; government institutions; legislator